Disease Caused by Phytium Spp. on Selected Crops Grown Under Hydroponic Culture System and Their Control - Chin, Chiew Lan (1988)
Large scale hydroponic crop production is a recent entity in Malaysia with University of Agriculture Malaysia (UPM) playing a lead role in research and development. Since its inception in 1982, pre- and post-emergent damping-off in cucumber, muskmelon and tomato seedlings had been frequently observed. Pythium spp. were also isolated from roots of wilted mature cucumber, muskmelon and tomato plants at UPM hydroponic, at Malaysia Agricultural Research and Development Institute (MARDI) and at FIMA hydroponic in Fraser's Hill. The mature muskmelon plants exhibited drastic interveinal chlorosis and yellowing of young and old leaves at the onset of fruiting and was accompanied by general necrosis of the root system resulting in subsequent plant death. Isolation of Pythium implicate them to be the causal agent. Since little is known about their role and control in the hydroponic system in Malaysia, studies were undertaken to characterize and identify the Pythium spp., to establish their pathogenicity, to determine the sources of inoculum, as well as to investigate the in-vitro and in-vivo efficacy of some fungicides in their control. Through cultural and morphological studies, three Pythium spp. namely P. myriotylum, P. splendens and a non-sporulating Pythium Spa were identified from six isolates obtained.